2012
DOI: 10.2298/tsci1204969h
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward dimensionless experimental formulae for flash point of binary mixtures of two flammable components

Abstract: Dimensionless experimental formulae based on a rational reciprocal function for correlation of flashpoint data of binary mixtures of two flammable components have been developed. The formulae are based on data obtained from flash-point experiments. The proposed approach requires only two coefficients, molar fraction of components and flashpoint temperatures of the pure flammable components to be known in advance. Literature data were used for formulae verification and validation obtained results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hertzberg (1982) reported that the flammability limits are correlated to a limiting laminar burning velocity (S u,lim ) that depends on the gaseous properties. More recently, Hristova et al (2012) correlated the flammability limits to the molar weight, as well as the boiling point, of the analysed substance. Finally, semi-empirical methodologies based on a thermal equilibrium theory, such as the adiabatic flame temperature method (Di Benedetto, 2013), based on the assumption of a constant value for the adiabatic flame temperature at flammability limits composition, have been proposed.…”
Section: State Of the Artmentioning
confidence: 99%
“…Hertzberg (1982) reported that the flammability limits are correlated to a limiting laminar burning velocity (S u,lim ) that depends on the gaseous properties. More recently, Hristova et al (2012) correlated the flammability limits to the molar weight, as well as the boiling point, of the analysed substance. Finally, semi-empirical methodologies based on a thermal equilibrium theory, such as the adiabatic flame temperature method (Di Benedetto, 2013), based on the assumption of a constant value for the adiabatic flame temperature at flammability limits composition, have been proposed.…”
Section: State Of the Artmentioning
confidence: 99%